1999
DOI: 10.1152/ajpregu.1999.277.5.r1385
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of branchial apical silver uptake by rainbow trout is via the proton-coupled Na+channel

Abstract: The branchial uptake mechanism of the nonessential heavy metal silver from very dilute media by the gills of freshwater rainbow trout was investigated. At concentrations >36 nM AgNO(3), silver rapidly entered the gills, reaching a peak at 1 h, after which time there was a steady decline in gill silver concentration and a resulting increase in body silver accumulation. Below 36 nM AgNO(3), there was only a very gradual increase in gill and body silver concentration over the 48-h exposure period. Increasing wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 26 publications
5
98
2
1
Order By: Relevance
“…Some research has shown that the mode of action of AgNPs on the invertebrate, Caenorhabditis elegans differs from their soluble counterpart, with the NPs affecting the reproduction potential and inducing a high level of oxidative stress (Roh et al, 2009). Ag + can reach the branchial epithelial cells via the Na + channel coupled to the proton ATPase in the apical membrane of the gills, then move to the basolateral membrane of the gill and block the Na + K + ATPtase affecting ion-regulation of Na + Cl -ions across the gill (Fabrega et al, 2011;Bury and Wood 1999). At high concentrations of Ag + , freshwater fish suffer circulatory collapse and death due to blood acidosis (Grosell et al, 1999;Hogstrand and Wood 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown that the mode of action of AgNPs on the invertebrate, Caenorhabditis elegans differs from their soluble counterpart, with the NPs affecting the reproduction potential and inducing a high level of oxidative stress (Roh et al, 2009). Ag + can reach the branchial epithelial cells via the Na + channel coupled to the proton ATPase in the apical membrane of the gills, then move to the basolateral membrane of the gill and block the Na + K + ATPtase affecting ion-regulation of Na + Cl -ions across the gill (Fabrega et al, 2011;Bury and Wood 1999). At high concentrations of Ag + , freshwater fish suffer circulatory collapse and death due to blood acidosis (Grosell et al, 1999;Hogstrand and Wood 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Silver ions or small AgNPs can easily enter the microbial body causing the damage of its intracellular structures. As a consequence ribosomes may be denatured with inhibition of protein synthesis, as well as translation and transcription can be blocked by the binding with the genetic material of the bacterial cell [33,59,60]. Protein synthesis has been shown to be altered by treatment with AgNPs and proteomic data have shown an accumulation of immature precursors of membrane proteins resulting in destabilization of the composition of the outer membrane [61].…”
Section: Salmonella Typhimentioning
confidence: 99%
“…ATPase which affects ionoregulation of Na ? Cl -ions across the gills (Bury and Wood 1999). Ag can also cause tissue damage and accumulate in the liver tissue affecting the ability of fish to cope with low oxygen levels and inducing oxidative stress (Bilberg et al 2010a, b;Scown et al 2010).…”
Section: Introductionmentioning
confidence: 99%